A Ferguson Effect, the Drug Epidemic, Both, or Neither? Explaining the 2015 and 2016 U.S. Homicide Rises by Race and Ethnicity. Issue 3 (August 2019) - Gaston, Shytierra; Cunningham, Jamein P.; Gillezeau, Rob
In 2015 and 2016, U.S. homicide rates rose dramatically amid two historic social phenomena: a police legitimacy crisis related to an alleged "Ferguson effect" and the opioid epidemic. To empirically explain this increase, we compile county-level data on race/ethnic-specific homicides from 2014 to 2016 along with contemporaneous county-level data on police killings of civilians, citizen protests, fatal drug overdoses, structural disadvantage, and other factors. Regression analysis suggests that both police illegitimacy and the drug epidemic contributed to Black and White homicide rises, particularly in structurally disadvantaged counties. However, we find no such association for Hispanic homicide increases.